Adverse cardiovascular effects of anti-tumor therapies in patients with breast cancer: a single-center cross-sectional analysis - Rosenkaimer, Stephanie L.; Sieburg, Tina; Winter, Laura; Mavratzas, Athanasios; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter; Akın, Ibrahim; Dürschmied, Daniel; Hohneck, Anna (Anticancer research, 2022)
Background/Aim: Cardiotoxicity due to antitumor therapy is a dreaded complication and could thus impact the prognosis of patients with breast cancer. This study sought to analyze the occurrence of adverse cardiovascular events and to identify potential risk factors. Patients and Methods: A total of 136 patients with breast cancer were divided into two groups based on the occurrence of treatment-related cardiovascular toxicity [event 47 (35%) vs. no event 89 (65%)]. Patients were followed over a median of 45 months (range=37-83 months). Results: Most common events were thromboembolic complications (26%), followed by heart failure (15%) and acute toxic cardiomyopathy (5%), with a reduced left ventricular ejection fraction [LVEF (%), no event 59±5.0 vs. event 55±11, p=0.01 ]. Patients with leftsided breast cancer and an advanced stage disease had a higher risk of developing adverse cardiovascular events. The highest risk was found for patients with a high number of cardiovascular risk factors. In addition to LVEF, mitral annular plane systolic excursion was also significantly reduced in the event group, while there was a trend for higher global longitudinal strain. During follow-up, 26 patients (19.1%) deceased, whereof 12 had a treatment-related cardiovascular event, but without statistical difference. Conclusion: Treatment-related cardiovascular events are relatively common in about one third of patients with breast cancer. Women with a cardiovascular risk profile or an advanced stage disease had a higher risk for adverse events. Despite the treatment-related cardiac deterioration, no difference in mortality was observed during follow up.